1961
DOI: 10.1139/v61-065
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Studies of Metallurgical Processes: Part I. The Thermal Reduction of Magnesium Oxide With Silicon

Abstract: The rate of reaction ( a ) has been studied over the temperature range 1140-1460' C, by following the loss in weight of the reactants in high vacuum.( a T h e loss in weight of the reactants was found to be greater than that which can be accounted for by the above reaction. The excess weight loss was found to be due to a brownish, glassy deposit which appeared outside the reaction zone. This material was analyzed by X-ray diffraction and found to be an intimate mixture of Mg?SiOs and Si. Experiments conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…SiO gas is stable a t these temperatures according to a number of investigators (23,24). In a previous publication (16), it was shown that SiO is distilled froill the reaction inixture of lMgO + Si a t temperatures above 1300" C. In the present work,…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…SiO gas is stable a t these temperatures according to a number of investigators (23,24). In a previous publication (16), it was shown that SiO is distilled froill the reaction inixture of lMgO + Si a t temperatures above 1300" C. In the present work,…”
Section: Discussionmentioning
confidence: 47%
“…The esperilnental procedure adopted for the determination of the reaction rate has been previously described (16). Briefly, the method consisted of deterlnining the weight loss with time of a briquetted reaction mixture due to the evolution of magnesium, by means of a calibrated helical steel \\lire spring suspended in a vacuum furnace.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process (Pidgeon and Alexander, 1944)-later known as the Pidgeon process-is based on reducing oxide of magnesium using silicon by supplying the thermal energy required for the reaction (Toguri and Pidgeon, 1961) as shown by the following equation:…”
Section: Pidgeon Processmentioning
confidence: 99%
“…[7] The silicothermic reduction of CaOMgO in the industrial Pidgeon process for magnesium was achieved by reacting CaO-MgO with ferrosilicon in evacuated retorts at 1450 K to 1800 K (1177°C to 1527°C) and less than 1.33 9 10 À4 bar. [8][9][10] The production of Si by vacuum carbothermal reduction of SiO 2 in the range 1997 K to 2263 K (1724°C to 1990°C) at 3 9 10 À3 bar yielded Si/SiO 2 mixtures condensed from the gas phase, with 79 wt pct Si content. [11] As will be shown in the following analysis, reaction [1] is highly endothermic (DH 298 K = 1344 kJ/mol) and proceeds at higher than approximately 1500 K (1227°C) when operating at 10 À4 bar.…”
Section: Introductionmentioning
confidence: 99%